The Effect of Applying Cow Dung Manure on Plant Growth and Yield Honey Gray (Cucurbita moschata L.) - Rostian nafery; Muhammad Andriyadi; Miranty Trinawaty; Meriyanto Meriyanto (Universitas Muhammadiyah Palembang, 2023)
This study aims to examine the effect of cow manure on the growth and yield of pumpkin honey (Cucurbita moschata L.). This research has been carried out in the Experimental Garden of the Faculty of Agriculture, Tridinanti University located in Pulau Semambu Village, North Indralaya District, Ogan Ilir Regency, South Sumatra Province. The study has been conducted from April 2023 to July 2023. The method used in this study is an experimental method, using Randomized Block Design (RBD) with 5 (five) treatments and 5 (five) repeats. Each unit consists of 20 plants so that the plants studied are 500 plants. The treatment in this study was P0 (without cow dung manure), P1 (10 tons of cow dung manure per hectare equivalent to 300 g per plant), P2 (20 tons of cow dung manure per hectare equivalent to 600 g per plant) P3 (30 tons of cow dung manure per hectare equivalent to 900 g per plant) and P4 (40 tons of cow dung manure per hectare equivalent to 1,200 g per plant). Based on the results of the study, it can be concluded that the application of cow dung manure has a good effect on the growth and yield of honey gourd plants. The application of cow dung manure P2 (20 tons/ha) resulted in the main length of the 1st month as high as 187.62 cm, the length of the main stem of the 2nd month as high as 327.16 cm, the length of the main trunk of the 3rd month as high as 367.36 cm, the number of primary branches 2.33 branches, flowering age 37 hst, the number of female flowers 63.30%, dry weight of plants 53.09 g, the number of fruits per plant 1.18 pieces, Fruit weight per plant 1.12 kg and fruit weight per plot 12.71 kg.